2016
DOI: 10.1149/2.0721609jes
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Electrolyte Pool Fires for Lithium Ion Batteries

Abstract: Combustion characteristics of electrolyte pool fires are investigated both theoretically and experimentally under various pan diameters and external heat fluxes using a cone calorimeter. The heat release rate (HRR), mass loss rate (MLR), flame height and gas release rate are measured. Experimental results show that the peak HRR and MLR per unit area are proportional to external heat fluxes and inversely proportional to pan diameters. Dimensionless flame height is observed to decrease under a bigger pan diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…EC [136] C In a scenario where there are different burning materials, then calorimetric principles can be utilized. These methods measure and rely on the consumption of oxygen or alternatively the generation of carbon monoxide or carbon dioxide.…”
Section: Solventmentioning
confidence: 99%
“…EC [136] C In a scenario where there are different burning materials, then calorimetric principles can be utilized. These methods measure and rely on the consumption of oxygen or alternatively the generation of carbon monoxide or carbon dioxide.…”
Section: Solventmentioning
confidence: 99%
“…The obvious self‐heating will drive the battery temperature rising constantly. In the meantime, the gases produced by side reaction and volatilization of electrolyte will bulk up the aluminum‐plastic film shell continuously 37,38 . According to the video, the cell expands to its maximum volume at 68864.6 seconds ( T 2 = 109.18°C) as Figure 4F shows.…”
Section: Results Of Thermal Runaway Testmentioning
confidence: 97%
“…It should be emphasized that the evaporation of electrolytes can be another reason for the swelling of the battery . It is reported that the boiling points of EMC and DEC are 110°C and 126°C ( Fu et al., 2016 ; Tang et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%